2018
DOI: 10.1371/journal.pone.0200092
|View full text |Cite
|
Sign up to set email alerts
|

Improved detectability of acute and subacute brainstem infarctions by combining standard axial and thin-sliced sagittal DWI

Abstract: Background and purposeMost false negative findings in DWI of ischemic stroke are in patients with minor deficits clinically localized to the brainstem. Our goal was to evaluate the benefit of a thin-sliced sagittal DWI in addition to conventional axial DWI at 1.5T for the detection of brainstem infarctions.MethodsData of patients with symptoms consistent with acute and subacute brainstem infarction and an MRI examination including standard axial DWI and thin-sliced sagittal DWI were retrospectively analyzed. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
(35 reference statements)
1
11
0
Order By: Relevance
“…Recently, it has been reported that combining standard axial and thin-sliced sagittal DWI improve the detectability of acute BI, although the cause of the improvement has not been studied. [19] In the present study, we also showed that the FN diagnosis of acute BI can be prevented by combining thin- section sagittal DWI with standard axial DWI. We found that the combination showed high sensitivity and specificity for the diagnosis of acute BI.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Recently, it has been reported that combining standard axial and thin-sliced sagittal DWI improve the detectability of acute BI, although the cause of the improvement has not been studied. [19] In the present study, we also showed that the FN diagnosis of acute BI can be prevented by combining thin- section sagittal DWI with standard axial DWI. We found that the combination showed high sensitivity and specificity for the diagnosis of acute BI.…”
Section: Discussionsupporting
confidence: 59%
“…The lesions were mainly located in the pons, consistent with a previous report. [8,19] When the second magnetic resonance imaging (MRI) was performed 7 days after the initial MRI, all six patients were shown to have infarction lesions on axial DWI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of vestibular symptoms, choosing the right MRI sequence is of the utmost importance: MRI according to a conventional stroke protocol is less sensitive than a HINTS-plus to detect small strokes causing vestibular symptoms [ 32 ]. Where a brainstem infarction is suspected, thin-sliced 3 mm diffusion-weighted imaging (DWI) sequences should be added, as they have a higher sensitivity for the detection of acute and subacute brainstem infarctions [ 33 ]. If imaging reveals an underlying pathology, targeted treatment can be initiated to reduce further invalidity.…”
Section: Discussionmentioning
confidence: 99%
“…The lesion was not restricted in DWIs and showed slightly high SI on the ADC map, further decreasing the likelihood of infarction [7 , 10] . The lesion showed predominantly low SI and slightly high SI on ADC.…”
Section: Discussionmentioning
confidence: 95%